Optimized Weighted Essentially Nonoscillatory Third-Order Schemes for Hyperbolic Conservation Laws - A. R. Appadu; A. A. I. Peer (Journal of Applied Mathematics)
We describe briefly how a third-order Weighted Essentially Nonoscillatory (WENO) scheme is derived by coupling a WENO spatial discretization scheme with a temporal integration scheme. The scheme is termed WENO3. We perform a spectral analysis of its dispersive and dissipative properties when used to approximate the 1D linear advection equation and use a technique of optimisation to find the optimal cfl number of the scheme. We carry out some numerical experiments dealing with wave propagation based on the 1D linear advection and 1D Burger’s equation at some different cfl numbers and show that the optimal cfl does indeed cause less dispersion, less dissipation, and lower L1 errors. Lastly, we test numerically the order of convergence of the WENO3 scheme.